Experts Opinion on the Practical Use of Azathioprine and 6-Mercaptopurine in Inflammatory Bowel Disease. Issue 11 (November 2016) - Mottet, Christian; Schoepfer, Alain M.; Juillerat, Pascal; Cosnes, Jacques; Froehlich, Florian; Kessler-Brondolo, Vera; Seibold, Frank; Rogler, Gerhard; Vavricka, Stephan R.; Michetti, Pierre
Abstract : Abstract: The relevance of azathioprine and 6-mercaptopurine therapy in inflammatory bowel disease, Crohn's disease, and ulcerative colitis, has been challenged in recent publications. In this article, a panel of experts gives advice, based on the relevant literature, on indications and practical use of azathioprine/6-mercaptopurine, prevention, and management of drug adverse reactions and special situations such as vaccination, pregnancy, and lactation. Abstract : Article first published online 7 October 2016.